New Perspectives on Glacial Geomorphology in Earth’s Deep Time Record - Le Heron, D. P.; Busfield, M. E.; Chen, X.; Corkeron, M.; Davies, B. J.; Dietrich, P.; Ghienne, J-F.; Kettler, C.; Scharfenberg, L.; Vandyk, T. M.; Wohlschlägl, R. (Frontiers in Earth Science, 2022)
The deep time (pre-Quaternary) glacial record is an important means to understand the growth, development, and recession of the global cryosphere on very long timescales (106-108 Myr). Sedimentological description and interpretation of outcrops has traditionally played an important role. Whilst such data remain vital, new insights are now possible thanks to freely accessible aerial and satellite imagery, the widespread availability and affordability of Uncrewed Aerial Vehicles, and accessibility to 3D rendering software. In this paper, we showcasedescribe examples of glaciated landscapes from the Cryogenian, Ediacaran, Late Ordovician and Late Carboniferous where this approach is revolutionizing our understanding of deep time glaciation. Although some problems cannot be overcome (erosion or dissolution of the evidence), robust interpretations in terms of the evolving subglacial environment can be made. Citing examples from Australia (Cryogenian), China (Ediacaran), North and South Africa (Late Ordovician, Late Carboniferous), and Namibia (Late Carboniferous), we point out the value of the “big picture” approach to illustrate how the power of glacial geomorphology can be harnessed to interpret in Earth’s ancient glacial record.